Current trends in exosome isolation methods: A systematic review - Morávek, Ondřej; Bílková, Zuzana (University of Pardubice, 2023)
Exosomes, extracellular vesicles crafted via a regulated process involving endocytosis, biomolecule packaging, and exocytosis, possess diverse functions. Exosomes participate in many processes crucial for the functionality of cells and tissues, e.g. in intercellular communication, immune response, programmed cell death, inflammation, and morphogen transport. Based on their multifunctional activity, the exosomes also play a significant role in many pathological conditions, such as malignancy or neurodegeneration. Nanosized exosomes carry various biomolecules as nucleic acids, proteins, lipids, metabolites. It has already been revealed that the composition of exosomes often corresponds with the (patho)physiological status of a cell, tissue, organ, and, ultimately, an organism. That is why the exosomes/oncosomes become promising structure suitable for studying the pathogenesis of the relevant disease or for the early and precise diagnosis of many serious diseases. The barrier for their wider use is the difficulty to isolate exosomes in the desired quantity and quality. To date, various isolation strategies have been proposed, spanning physico-chemical and affinity-based methods. Even the accelerated exosome isolation techniques exploiting the benefits of magnetic carriers or microfluidic platforms are still facing some limitations, and it is already clear where new trends can be expected. A concise review of strategies and technologies for exosome isolation is given here.
Keywords: extracellular vesicles; exosome; isolation; physicochemical methods; affinity-based methods; microfluidics